Narava, kultura in etika okolja - Rolston, Holmes, 1932-2025, author; Institute of Landscape Architecture, University of Ljubljana, publisher (Colorado State University. Libraries, 1996)
Humans in their cultures are out of sustainable relationships to the natural environments on which these cultures are superimposed. Bringing such culture into more intelligent relationships with the natural world requires not so much "naturalizing culture" as discriminating recognition of the radical differences between nature and culture, on the basis of which an ethic of complementarity may be possible. How far nature can and ought be transformed into humanized nature is a provocative question. Environmental ethics ought also to seek nature as an end in itself.
Nature and culture in environmental ethics
Nature, culture, and environmental ethics
Text in Slovenian.
Keywords: environmental ethics; ecology; ecosystems; humans; culture; sustainability